Microbiology of fresh water fish - Khair, Jamil; Rusul, Gulam; Hassan, Zaiton (1983)
A quantitative and qualitative determination of the bacterial flora on the skin of fresh and refrigerated (8-9⁰C) of 3 species of freshwater fish which were obtained from Majuikan at Puchong were carried out. The fish were 'Lampam Jawa' (Puntius gonionotus), 'patin'(pangasuis sutchi) and 'jelawat' (Leptobarbus hoevenii). The fish were wrapped in plastic bags and refrigerated for 14 days, during which samples were taken every 2 days for microbiological analysis and physical changes.